Individual Sea Urchin Coelomocytes Undergo Somatic Immune Gene Diversification - Oren, Matan; Rosental, Benyamin; Hawley, Teresa S.; Kim, Gi-Young; Agronin, Jacob; Reynolds, Caroline R.; Grayfer, Leon; Smith, L. Courtney (Frontiers in Immunology, 2019)
The adaptive immune response in jawed vertebrates is marked by the ability to diversify somatically specific immune receptor genes. Somatic recombination and hypermutation of gene segments are used to generate extensive repertoires of T and B cell receptors. In contrast, jawless vertebrates utilize a distinct diversification system based on copy choice to assemble their variable lymphocyte receptors. To date, very little evidence for somatic immune gene diversification has been reported in invertebrate species. Here we show that the SpTransformer (SpTrf ; formerly Sp185/333) immune effector gene family members from individual coelomocytes from purple sea urchins undergo somatic diversification by means of gene deletions, duplications, and acquisitions of single nucleotide polymorphisms. While sperm cells from an individual sea urchin have identical SpTrf gene repertoires, single cells from two distinct coelomocyte subpopulations from the same sea urchin exhibit significant variation in the SpTrf gene repertoires. Moreover, the highly diverse gene sequences derived from single coelomocytes are all in-frame, suggesting that an unknown mechanism(s) driving these somatic changes involve stringent selection or correction processes for expression of productive SpTrf transcripts. Together, our findings infer somatic immune gene diversification strategy in an invertebrate.